2023
DOI: 10.1021/acs.jmedchem.3c00308
|View full text |Cite
|
Sign up to set email alerts
|

Linearization of the Brevicidine and Laterocidine Lipopeptides Yields Analogues That Retain Full Antibacterial Activity

Abstract: Brevicidine and laterocidine are macrocyclic lipodepsipeptides with selective activity against Gram-negative bacteria, including colistin-resistant strains. Previously, the macrocyclic core of these peptides was thought essential for antibacterial activity. In this study, we show that C-terminal amidation of linear brevicidine and laterocidine scaffolds, and substitution of the native Thr9, yields linear analogues that retain the potent antibacterial activity and low hemolysis of the parent compounds. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We focused our study on a small library of analogues ( 4 – 8 , Scheme ), specifically investigating the effect of increasing the net positive charge and hydrophobicity of the exocyclic sequence. Previous SAR studies on 1 have implicated the effect these factors have on the bioactive conformation of the native peptide, thus prompting us to explore whether these observations could explain the underlying mechanism of action of 2 . , The syntheses of analogues 4 – 8 were achieved following a similar route to that used for the synthesis of 2 with substitution of Fmoc- d -Phe-OH at position-two for the appropriate commercially available amino acids during the sequence elongation stage (Scheme ). Notably, the synthetic analogues investigated in this study are mixtures of the C-4 lipid epimer achieved through the coupling of ( R,S )-4-methylhexanoic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our study on a small library of analogues ( 4 – 8 , Scheme ), specifically investigating the effect of increasing the net positive charge and hydrophobicity of the exocyclic sequence. Previous SAR studies on 1 have implicated the effect these factors have on the bioactive conformation of the native peptide, thus prompting us to explore whether these observations could explain the underlying mechanism of action of 2 . , The syntheses of analogues 4 – 8 were achieved following a similar route to that used for the synthesis of 2 with substitution of Fmoc- d -Phe-OH at position-two for the appropriate commercially available amino acids during the sequence elongation stage (Scheme ). Notably, the synthetic analogues investigated in this study are mixtures of the C-4 lipid epimer achieved through the coupling of ( R,S )-4-methylhexanoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, our findings suggest that increasing the net positive charge from +3 to +4 is not beneficial, suggesting a preference for the presence of a hydrophobic residue at position-two. This result is consistent with the findings of the Martin group when studying 1 . In their study, an alanine scan showed that both the hydrophobic and cationic residues in positions 2–8 of the N-terminal exocyclic tail were integral for target binding and maintaining an active conformation to cross the bacterial cell membrane.…”
Section: Resultsmentioning
confidence: 99%